Gender perspective as an element of multilevel constitutionalism: an analysis based on the jurisprudence of the court of justice of Rio Grande do Norte - De Araújo Costa, Milena; Canuto, Érica (Revista de Derecho Público, 2023)
Based on multilevel feminist constitutionalism, the question arises, does the Superior Court of Justice of Rio Grande do Norte really comply with the 2021 Protocol for judging with a gender perspective? Thus, this research examines the gender perspective as an element of multilevel constitutionalism, analyzes the legislation that contributes to the implementation of the aforementioned protocol and, finally, reviews the jurisprudence of the Superior Court of Justice to assess whether it is judging with a gender perspective.